Associating Cognition With Amyloid Status Using Partially Ordered Set Analysis - Carr, Sarah J.A.; Jaeger, Judith; Bian, Shijia; He, Ping; Maserejian, Nancy; Wang, Wenting; Maruff, Paul; Enayetallah, Ahmed; Wang, Yanming; Chen, Zhengyi; Lerner, Alan; Tatsuoka, Curtis; et al. (Frontiers in Neurology, 2019)
Background: The presence of brain amyloid-beta positivity is associated with cognitive impairment and dementia, but whether there are specific aspects of cognition that are most linked to amyloid-beta is unclear. Analysis of neuropsychological test data presents challenges since a single test often requires drawing upon multiple cognitive functions to perform well. It can thus be imprecise to link performance on a given test to a specific cognitive function. Our objective was to provide insight into how cognitive functions are associated with brain amyloid-beta positivity among samples consisting of cognitively normal and mild cognitively impaired (MCI) subjects, by using partially ordered set models (POSETs). Methods: We used POSET classification models of neuropsychological test data to classify samples to detailed cognitive profiles using ADNI2 and AIBL data. We considered 3 gradations of episodic memory, cognitive flexibility, verbal fluency, attention and perceptual motor speed, and performed group comparisons of cognitive functioning stratified by amyloid positivity (yes/no) and age (< 70, 70 – 80, 81 – 90 y). We also employed random forest methods stratified by age to assess the effectiveness of cognitive testing in predicting amyloid positivity, in addition to demographic variables and APOE4 allele count. Results: In ADNI2, differences in episodic memory and attention by amyloid were found for < 70, and 70 – 80 y groups. In AIBL, episodic memory differences were found in the 70 – 80 y age group. In both studies, no cognitive differences were found in the 81 – 90 y group. The random forest analysis indicates that variable importance in classification depends on age. Cognitive testing that targets an intermediate level of episodic memory and delayed recall, in addition to APOE4 allele count, are the most important variables in both studies. Conclusions: In the ADNI2 and AIBL samples, the associations between specific cognitive abilities and brain amyloid-beta positivity depended on age, but in general episodic memory was most consistently predictive of brain amyloid-beta positivity. Random forest methods and OOB error rates establish the feasibility of predicting the presence of brain beta-amyloid using cognitive testing, APOE4 genotyping and demographic variables.